Information visualization and technology. Emergence and progress of AI in commercial and code proposals - Pérez-Montoro, Mario (Anuario ThinkEPI, 2023)
Since its origins, the discipline of information visualization has always walked hand in hand with related technological advances and their evolution. Today, there is a wide variety of software tools and technologies, some using code and some commercial, that allow users to effectively visualize and analyze data. Artificial intelligence and machine learning may also revolutionize the way information is visualized, allowing users to explore, in a more comfortable and efficient way, patterns and trends in large datasets.
Keywords: Information visualization; Visual communication; Data visualization; Technology; Trends; Interactive visualization; 2022